Sovereign Screens : Aboriginal Media on the Canadian West Coast. - Dowell, Kristin L. (UNP - Nebraska, 2013)
While Indigenous media have gained increasing prominence around the world, the vibrant Aboriginal media world on the Canadian West Coast has received little scholarly attention. As the first ethnography of the Aboriginal media community in Vancouver, Sovereign Screens reveals the various social forces shaping Aboriginal media production including community media organizations and avant-garde art centers, as well as the national spaces of cultural policy and media institutions. Kristin L. Dowell uses the concept of visual sovereignty to examine the practices, forms, and meanings through which A.